Differential IL-18 Dependence of Canonical and Adaptive NK Cells for Antibody Dependent Responses to P. falciparum - Sherratt, Samuel; Patel, Avnish; Baker, David A.; Riley, Eleanor M.; Goodier, Martin R. (Frontiers in Immunology, 2020)
Human adaptive natural killer (NK) cells have diminished reliance on accessory cytokines for their activation whilst being efficiently activated by infected host cells in conjunction with pathogen specific antibodies. Here, we show that potent antibody-dependent NK cell responses are induced by Plasmodium falciparum infected erythrocytes (iRBC) in peripheral blood mononuclear cells (PBMC) from malaria-exposed Gambian individuals in the presence of autologous sera, which are absent in those from malaria-naïve UK individuals. However, malaria hyper-immune serum promotes rapid NK cell responses to iRBC in cells from both Gambian and UK individuals. Among Gambians, highly differentiated, adaptive (CD56dimFceR1g-CD57+) NK cells dominate both antibody-dependent NK cell IFN-g responses and degranulation responses, whereas among UK individuals these responses are predominantly found within canonical, highly differentiated CD56dimFceR1g+CD57+ NK cells. Indeed, overall frequencies of adaptive, FceR11-CD57+ NK cells are significantly higher among Gambian donors compared to HCMV-infected and HCMV-uninfected UK adults. Among UK individuals, antibody-dependent NK cell IFN-g responses to iRBC were dependent on IL-18 whereas among Gambians, the predominant adaptive FceR1g- NK cell response was IL-18 (and accessory cell) independent (although the lower frequency response of canonical FceR1g+NK cells did rely on this cytokine).